HISTOPATHOLOGICAL STUDY ON WHITE RATS’ GASTRIC GIVEN PARACETAMOL AND PROPOLIS SUPPLEMENTATION - Maria, Noviriolla; Berata, I Ketut; Kardena, I Made; Samsuri, Samsuri (Buletin Veteriner Udayana, 2017)
Propolis is a substance produced by bees that has some benefits, such as: antioxidants and antiulkus. Paracetamol is a relatively safe drug for gastric, but in some studies claimed that high doses of paracetamol increase the risk of gastric mucosal disorders, such as: ulceration, desquamation, and erosion. The purpose of this study is to determine the effects of propolis in histopathological gastric rats that were given high doses of paracetamol. This study used a completely randomized design. A sample of 25 male rats were divided into 5 groups i.e.: a negative control without treatment paracetamol (P0), a positive control (P) that was given paracetamol 250 mg/kgbw, and three other groups given treatment with paracetamol 250 mg/kgbw with a variation of propolis,  P1 (0.05 ml/rat), P2 (0.10 ml/rat), and P3 (0.15 ml/rat). The treatment was given in 10 days, then necropsy was done and gastric organs were taken. Histologic gastric specimen for histopathological examination was made by using the Kiernan method (1990) and stained with hematoxylin eosin (HE). Variables examined include histopathological lesions of erosion, desquamation, and ulceration of the gastric epithelium. Results indicate that in treatment P severe damage to the gastric (desquamation) has occurred, while the entire treatment P1, P2, and P3 show the repair from the damage caused by the paracetamol. Treatment P3 gives the best results in reducing the effects of the paracetamol. This study concluded  that the provision of propolis may reduce the histopathological side effects on  white rat’s gastric givenhigh dose of paracetamol.
Keywords: parasetamol; propolis; antioksidan, antiulkus; lambung